Malaysian private general practitioners' views and experiences on continuous professional development: a qualitative study - Abdul Samad, Norlehan; Md Zain, Aishah; Osman, Rozimah; Lee, Ping Yein; Ng, Chirk Jenn (Academy of Family Physicians of Malaysia, 2014)
Introduction: Continuous professional development (CPD) is an important aspect of a medical practitioner’s career. Aiming to be at par with other developed countries for high quality of professional practice, Malaysia is planning to implement compulsory CPD for the doctors. Aim: The aim of the study was to explore the private general practitioners’ (GPs) views, experiences and needs regarding CPD programme in the primary care service. Methods: This study used a qualitative methodology. Seven semi-structured interviews and three focus group discussions were conducted with private general practitioners from an urban area of Malaysia between January and December 2012. An interview topic guide was developed based on literature review and researchers’ discussions and it was used to guide the interviews. All the interviews were audio-recorded, transcribed verbatim and the transcripts formed the data for analysis using the thematic approach. Results: GPs undertook a wide range of CPD programmes to keep up with medical advances, meet patients’ expectations and improve financial rewards. Conferences, lectures and online recourses were the most mentioned methods of keeping updated. Some of the GPs felt that peer motivation and networking seem to motivate and facilitate participation in CPD programmes. However, they were wary of the validity and relevance of some CPD programmes, particularly those related to pharmaceutical industry. Although the participants agreed to the new mandatory CPD regulation, they voiced concerns on how it would be implemented and wished for a more effective method of monitoring. Conclusions: Organised peer support and relevant CPD content may improve GP participation in CPD but adequate regulatory measure should be in place to monitor the CPD activities.